The logic of discipline global capitalism and the architecture of government - Roberts, Alasdair (Alasdair Scott) (New York ; Oxford : Oxford University Press, 2010)
A sweeping account of neoliberal governmental restructuring across the world, 'The Logic of Discipline' offers a powerful analysis of how this undemocratic model is unraveling in the face of a monumental-and ongoing-failure of the market.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Capitalism -- Political aspects; Democracy -- Economic aspects; International finance -- Political aspects; Democratization